Brazilian Economic Performance since the Emergence of the Great Recession: The Effects of Income Distribution on Consumption - Arestis, Philip; Baltar, Carolina Troncoso; Prates, Daniela Magalhães (Panoeconomicus, 2016)
After a long period of unstable and low economic activity, Brazil achieved a relatively high economic growth with low inflation from 2004 to 2008, when the world scenario was favourable for the Brazilian trade balance. An incomes policy, focused on real increases in the minimum wage along with a credit boom, led to a decade of high consumption growth rates. High levels of consumption and exports, in turn, induced investment and stimulated manufacturing production, despite the real appreciation of the national currency. However, the Great Recession that emerged after the global financial crisis of 2007/2008 brought challenges to the Brazilian economic performance, with unpleasant consequences for the country’s GDP growth. Consumption, investment and exports have decelerated, despite anti-cyclical macroeconomic policies. In this setting, manufacturing production stagnated and GDP growth slowed down substantially, while imports continued rising considerably. The aim of this paper is to provide an explanation to the slowdown of Brazilian growth rates after the Great Recession. The main hypothesis is that consumption was the main source of effective demand in the country since 2003. However, Brazil has not yet been able to sustain manufacturing and economic growth without a more active government policy to stimulate productive investment.Key words: Income distribution, Consumption, Imports, Investment.JEL: E21, E25, F1.